Internalisasi Budaya Kerja Berbasis Al-Fatihah dalam Meningkatkan Kinerja pada Tenaga Kependidikan - Harjani Hefni; Fitri Sukma Wati; Santa Rusmalita (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2019)
This research aims to evaluate the effectiveness of working culture internalization based on Alfatihah in order to encourage performance among educational employee through mixed method with quntitative-qualitative paradigm. Result shows that there is a significant differences on means of employee performance in which before having treatment and after having treatment. Therefore, treatment method with Alfatihah effectively increased performance of educational employee. This research is expected to be used as an input to develop positive working culture.